Driving innovation and business success in the digital economy - Oncioiu, Ionica, 1972- (Business Science Reference, 2016)
"This book is an essential reference source for the latest research on the impact of digital computing and emerging technological innovations in the realm of business success. Featuring extensive coverage across a range of relevant perspectives and topics, such as IT outsourcing, sustainable development and online advertising"- Resumé vydavatele
Keywords: informační technologie; management; inovace; information technology; innovations; kolektivní monografie; elektronické knihy; collective monographs; electronic books